2003
DOI: 10.1111/j.1349-7006.2003.tb01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fas in malignant pleural effusion and its expression in lung cancer cells

Abstract: as (APO-1, CD95) is a 48-kDa type I transmembrane protein which belongs to the TNF (tumor necrosis factor) receptor superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…Similar results have been shown in human hepatocellular carcinoma and human lung cancer cell lines [21,22]. The concentrations of soluble Fas/APO-1 antigen in HeLa cell line culture with all-trans-retinoic acid (ATRA) were downregulated when compared with HeLa cell line without ATRA.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results have been shown in human hepatocellular carcinoma and human lung cancer cell lines [21,22]. The concentrations of soluble Fas/APO-1 antigen in HeLa cell line culture with all-trans-retinoic acid (ATRA) were downregulated when compared with HeLa cell line without ATRA.…”
Section: Discussionsupporting
confidence: 77%
“…After incubation for the indicated periods, all cells were collected, washed with PBS (-), and lysed with 1 ml of isogen (Nippon Gene). Total RNA was then extracted as described previously (25). HUVECs were used as a positive control.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…The human lung adenocarcinoma PC-14 was a generous gift from Dr. N. Saijo (National Cancer Institute, Tokyo, Japan) (25). The cell line was maintained in RPMI 1640 medium supplemented with 10% FBS and penicillin/streptomycin (designated as CRPMI-1640) in a humidified incubator with a 5% CO 2 atmosphere at 37°C.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Similarly, the soluble Fas protein, which is able to inhibit the immunogenic cells that will kill the tumor cells in its tumoral area, exists at a higher level in the malignant pleural effusions resulting from the lung cancer than the pleural effusions that emerged due to a reason other than cancer. Moreover, it was found that the soluble Fas was expressed by many lung cancer cell lines, such as H69, N291, RERF-LC-OK (Kagi et al, 1994;Mitani et al, 2003). It was determined that expression of the vascular endothelial growth factor (VEGF) was 10 times higher in the effusions of the patients with ovary, breast, and gastrointestinal carcinoma than that of the paired serum (Kraft et al,1999).…”
mentioning
confidence: 99%